2018
DOI: 10.1093/ejcts/ezy169
|View full text |Cite
|
Sign up to set email alerts
|

Statistical primer: sample size and power calculations—why, when and how?†

Abstract: When designing a clinical study, a fundamental aspect is the sample size. In this article, we describe the rationale for sample size calculations, when it should be calculated and describe the components necessary to calculate it. For simple studies, standard formulae can be used; however, for more advanced studies, it is generally necessary to use specialized statistical software programs and consult a biostatistician. Sample size calculations for non-randomized studies are also discussed and two clinical exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(69 citation statements)
references
References 25 publications
0
67
0
2
Order By: Relevance
“…All analyses were evaluated with SPSS version 20.0 (SPSS 20.0, IBM, USA). A power analysis was conducted with PASS 19.0 to calculate the number of subjects needed in this study; PASS (https ://www.ncss.com/softw are/pass) is a professional software used to calculate sample size [42]. We found that the incidence of increased CIMT in patients with T2DM was 23.5% in a study conducted in a Chinese population [27].…”
Section: Discussionmentioning
confidence: 99%
“…All analyses were evaluated with SPSS version 20.0 (SPSS 20.0, IBM, USA). A power analysis was conducted with PASS 19.0 to calculate the number of subjects needed in this study; PASS (https ://www.ncss.com/softw are/pass) is a professional software used to calculate sample size [42]. We found that the incidence of increased CIMT in patients with T2DM was 23.5% in a study conducted in a Chinese population [27].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical characteristics, the proportion of severe patients and the mortality of patients with COVID-19 are different according to different individual publications. The main reason for the differences in different studies is that the sample size of each study is small with limited statistical power [30].…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was calculated with a significance between treatment and placebo groups at P = .05 and a power of 80% using the result of body fat mass and percentage reported by Nosaka et al 24 The required number of subjects was determined using a power calculation according to published guidelines for human dietary intervention studies. 25,26 The Sinetrol-XPur and placebo tablets were provided by the investigators every 6 weeks, and compliance was assessed at every follow-up. Compliance was monitored through a trained researcher by calculating remnant tablet strips from the participants at the third and fourth visits.…”
Section: Methodsmentioning
confidence: 99%